Impacts of EL NIÑO-Southern oscillation on tropical cyclone activity over the coastal zones of Vietnam - Nguyen Thanh, Co; Hoang Luu Thu, Thuy; Dinh Van, Manh; Trinh Thi Thu, Thuy (Vietnam Journal of Earth Sciences, 2024)
The activity of El Niño - Southern Oscillation (ENSO) has been found to alter the characteristics of tropical cyclones (TCs) worldwide. This paper examines how ENSO influences the active time, occurence frequencies, and intensities of TCs over the coastal zones of Vietnam. The study uses Best Track Data in the Western North Pacific region from 1961 to 2020. The wind speed fields of all TCs over the coastal zones are calculated using a semi-empirical model with a square grid of 0.05° resolution. The results show that the frequencies of TCs over the coastal zones decrease during El Niño years, whilethe TC intensities increase significantly compared to those in Neutral years. Meanwhile, TC intensities over all coastal zones during La Niña years, and some coastal zones during El Niño years, decrease significantly compared to those in Neutral years. The magnitudes of both the increase and decrease in TC frequencies and intensities over the coastal zones vary significantly. Moreover, the active time of TCs during La Niña years in some coastal zones is shorter and occurs later than during the Neutral years.